Resiliensi Remaja Muslim di Era Digital: Peran Bimbingan Konseling Islam dalam Pencegahan Krisis Moral - Oktio Frenki Biantoro; Alfan Arifuddin (Program Studi Bimbingan dan Konseling Islam, 2025)
This study examines strategies for building resilience among Muslim youth in the digital age through the Islamic Guidance and Counseling (BKI) approach. Using a literature review method, the study identifies that resilience is formed through the synergy of internal aspects (such as emotional regulation, husnuzhan, patience, gratitude, and tawakal) and external aspects (family support, pious peers, and positive communities). ICG interventions play a vital role in facilitating the strengthening of self-capacity (I Am), social support (I Have), and problem-solving skills (I Can) based on Islamic spiritual values. As a result, this holistic approach is effective in building adolescents' mental-spiritual resilience, preventing maladaptive behaviors, and guiding them toward psychological well-being (sa'adah fid-darain) amid the challenges of the digital world.